Family as a Context of Informal Education - Popović, Daliborka R.; Minić, Vesna Lj.; Popović, Milica D. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Due to the changed social circumstances and the growing role of informal education in the process of personal development, the aim of the paper is to consider the importance of family activities, which hold the most dominant role in informal education. The key premise of modern society must therefore be based on establishing continuity in the process of lifelong learning, through the necessity of a holistic relationship between education and society. It is important to move away from the classical way of understanding the education as a process of knowledge transfer that takes place in the formal context and focus on the fact that learning is not limited by time, space, and institution. Starting from the fact that the family is the first and foremost system for a child, only with changed roles in different life cycles, an attempt was made to point out key effects on the family, but also on the child by the family, primarily for prosocial development. Prosocial development takes place by modelling behaviours through which the desired value system is expressed and instilled in a child. Regarding the family as educators in informal education, the paper emphasizes the need to monitor procedures that have a scientific and professional basis, with caution against “falling under the influence” of implicit theories of education that are promoted on social networks and in other, modern forms of social groups. In that sense, the necessity of supporting the family in educational activities, which represent the core of informal education in the family context, is emphasized. After considering the basic principles of formal, non-formal and informal education, the paper emphasizes the growing importance of informal education and the role of the family in this process, considering the key settings of parenting for holistic personality development, based on Kant’s claim to educate. Namely, the attention was drawn to the educational activities of the family in the process of individual and social development through an informal approach, as well as to the questions of its competence to respond to the challenges posed by the social change.